The crosstalk within the breast tumor microenvironment in type II diabetes: Implications for cancer disparities - Ennis, Christina S.; Llevenes, Pablo; Qiu, Yuhan; Dries, Ruben; Denis, Gerald V. (Frontiers in Endocrinology, 2022)
Obesity-driven (type 2) diabetes (T2D), the most common metabolic disorder, both increases the incidence of all molecular subtypes of breast cancer and decreases survival in postmenopausal women. Despite this clear link, T2D and the associated dysfunction of diverse tissues is often not considered during the standard of care practices in oncology and, moreover, is treated as exclusion criteria for many emerging clinical trials. These guidelines have caused the biological mechanisms that associate T2D and breast cancer to be understudied. Recently, it has been illustrated that the breast tumor microenvironment (TME) composition and architecture, specifically the surrounding cellular and extracellular structures, dictate tumor progression and are directly relevant for clinical outcomes. In addition to the epithelial cancer cell fraction, the breast TME is predominantly made up of cancer-associated fibroblasts, adipocytes, and is often infiltrated by immune cells. During T2D, signal transduction among these cell types is aberrant, resulting in a dysfunctional breast TME that communicates with nearby cancer cells to promote oncogenic processes, cancer stem-like cell formation, pro-metastatic behavior and increase the risk of recurrence. As these cells are non-malignant, despite their signaling abnormalities, data concerning their function is never captured in DNA mutational databases, thus we have limited insight into mechanism from publicly available datasets. We suggest that abnormal adipocyte and immune cell exhaustion within the breast TME in patients with obesity and metabolic disease may elicit greater transcriptional plasticity and cellular heterogeneity within the expanding population of malignant epithelial cells, compared to the breast TME of a non-obese, metabolically normal patient. These challenges are particularly relevant to cancer disparities settings where the fraction of patients seen within the breast medical oncology practice also present with co-morbid obesity and metabolic disease. Within this review, we characterize the changes to the breast TME during T2D and raise urgent molecular, cellular and translational questions that warrant further study, considering the growing prevalence of T2D worldwide.